An anti-spot, high-precision subdivision algorithm for linear CCD based single-track absolute encoder. (April 2019) - Yuan, Pengfei; Huang, Daqing; Lei, Zhongkui; Xu, Cheng
Highlights: An unique robust subdivision algorithm for single-track absolute encoder is proposed. Robustness relies on decomposition of correlated information from multiple grid lines. Standard deviation of subdivision output is improve from 5 . 7 ″ to 0 . 9 ″ by test. Abstract: To improve precision performance of angular sensor, in this paper, research is performed on subdivision technology for a single-track absolute photoelectrical encoder. Firstly, a robust subdivision algorithm is proposed by means of processing a feature matrix of measurement which is created from multiple grating lines' image. Secondly, simulation of anti-noise and anti-spot is established to prove that the proposed algorithm is robust theoretically. Finally, the algorithm is applied in a photoelectrical encoder for real tests, experiment result shows that the subdivision algorithm proposed in this paper is more accurate and adaptive than the traditional way. To reduce a negative precision effect caused by noises and spots, it measures angle according to multiple grating lines by assigning different weights, making those grating lines deeply noised with lower weight, and higher weight with minor noise, thus the overall accuracy is improved. With the proposed subdivision algorithm, test encoder's standard deviation of error can be increased to 1 . 6 ″ and precision achieves up to ± 0 . 9 ″ .